PERAN HUKUM ADAT DALAM PENEGAKAN KETERTIBAN MASYARAKAT PERSPEKTIF HUKUM ISLAM - Endah, Ranti Suminar; Shaleh, Muhammad Noor (Mitsaqan Ghalizan, 2024)
In many indigenous communities, disputes are usually resolved through deliberation or a family approach involving traditional leaders, religious leaders or respected third parties. In this process, efforts are made to reach a solution that is favorable to all parties, without considering who is right or wrong, but rather the goal of restoring peace and harmony in the community. On the other hand, in the perspective of Islamic law, dispute resolution is seen from the point of view of justice based on the principles of sharia. The plurality of laws is interesting to review how they harmonize in their role in regulating community order. This research uses qualitative research methods classified as normative legal research with a conceptual approach. The results of this study indicate that customary law is one of the bases for judges to decide a case based on the law if the judge does not find a basis for deciding on written law. Enforcement of public order is also seen as a very important obligation from the perspective of Islamic law. Islamic law provides a clear outline of how to build a just, safe and peaceful society.